Learning Style and Interaction Preference: Application of Moore's Typology - Johnson, Genevieve (AACE, 2011)
Moore’s (1989) typology of interaction (i.e., learner-learner, learner-instructor, and learner-content) is applied to assess and explore student interaction preference. Ninety-three college students in a hybrid educational psychology course completed a questionnaire that assessed learning style and interaction preference. Permission was obtained to use student grades for research purposes. Most students expressed the perception that the instructor and course content were most critical to their learning; a minority reported that other students most contributed to their learning. Students with active and global learning styles preferred learner-learner interaction. Students who expressed the perception that other students most contributed to their learning tended toward academic under-achievement. Contextual and individual variables require consideration in e-learning applications of Moore’s typology.